Amyotrophic lateral sclerosis among patients with a Medicare Advantage prescription drug plan; prevalence, survival and patient characteristics. Issue 3 (3rd April 2019) - Bhattacharya, Rituparna; Harvey, Raymond A.; Abraham, Keli; Rosen, Jon; Mehta, Paul
Abstract: Objective : To estimate amyotrophic lateral sclerosis (ALS) prevalence, 5-year survival, and explore factors associated with survival in a Medicare population. Methods : A validated administrative claims algorithm was used to classify individual's ages 18–89 years at index date (first claim with a diagnosis of motor neuron disease or ALS between 1 January 2007 and 31 December 2011) with Medicare Advantage prescription drug coverage into mutually exclusive categories: ALS, no ALS, and possible ALS. Crude prevalence and cumulative survival from index date to the date of death, disenrollment or end of the study were calculated. Cox-proportional hazards were used to estimate and explore factors associated with survival. Results : Of 2631 eligible individuals, the algorithm identified 1271 (48 %), 1157 (44 %), 203 (8 %) as ALS, no ALS and possible ALS, respectively. The 5-year period prevalence and the 2011 point prevalence of ALS were 20.5 and 11.8 per 100, 000, respectively. Evidence of death was documented in 81%, 35%, and 1.6% of the ALS, no ALS or possible ALS groups, respectively. Unadjusted median survival time was 388, 542 and 1473 days for the ALS, no ALS and possible ALS groups, respectively. Seeing a psychiatrist or neurologist at the index visit, having respiratory or genitourinary comorbidities, and the number of pre-index acute inpatient admissions were associated with shorter survival. Conclusions : Surveillance data from a Medicare population demonstrated a higher prevalence of ALS. Results highlight the need for effective ALS treatment options and resources for patients with ALS who will likely face limited therapeutic choices and care options at the end of life.